The 10th anniversary of the scientific description of the black snub‐nosed monkey (Rhinopithecus strykeri): It is time to initiate a set of new management strategies to save this critically endangered primate from extinction. Issue 6 (8th March 2022) - Yang, Yin; Lin, Aung Ko; Garber, Paul A.; Huang, Zhipang; Tian, Yinping; Behie, Alison; Momberg, Frank; Grueter, Cyril C.; Li, Weibiao; Lwin, Ngwe; Xiao, Wen
Abstract: Traditionally, the genus Rhinopithecus (Milne‐Edwards, 1872, Primates, Colobinae) included four allopatric species, restricted in their distributions to China and Vietnam. In 2010, a fifth species, the black snub‐nosed monkey ( Rhinopithecus strykeri ) was discovered in the Gaoligong Mountains located on the border between China and Myanmar. Despite the remoteness, complex mountainous terrain, dense fog, and armed conflict that characterizes this region, over this past decade Chinese and Myanmar scientists have begun to collect quantitative data on the ecology, behavior and conservation requirements of R. strykeri . In this article, we review the existing data and present new information on the life history, ecology, and population size of R. strykeri . We discuss these data in the context of past and current conservation challenges faced by R. strykeri, and propose a series of both short‐term and long‐term management actions to ensure the survival of this Critically Endangered primate species. Specifically, we recommend that the governments and stakeholders in China and Myanmar formulate a transboundary conservation agreement that includes a consensus on bilateral exchange mechanisms, scientific research and monitoring goals, local community development, cooperation to prevent the hunting of endangered species and cross‐border forest fires. These actions will contribute to the long‐term conservation and survival of this Critically Endangered species. Abstract : This study evaluated conservation status and recommended policies and conservation actions for the Critically Endangered black snub‐nosed monkey ( Rhinopithecus strykeri ) in Sino‐Myanmar border. Highlight: We confirmed the existence of at least six remaining groups, totaling between 520 and 600 individuals, of the Critically Endangered black snub‐nosed monkey ( Rhinopithecus strykeri ) in the Gaoligong Mountains on the Sino‐Myanmar border. We examined the present conservation challenges faced by the world's last remaining population of this species, and offer a set of new management strategies to ensure its continued survival.